Vehicle emissions testing: failure probabilities, repair incentives, and policy assessment - Kemp, Rula Qalyoubi, author; Revier, Charles F., advisor; Jianakoplos, Nancy, committee member; Kling, Robert, committee member; Loomis, John B., committee member (Colorado State University. Libraries, 2005)
The Environmental Protection Agency (EPA) entrusted with mobile emissions attainment has enacted rules in the form of regulations on automobile manufacturers complemented with periodic emissions inspection. The aim of I/M programs is to ensure that vehicles operating in I/M regions have functioning emissions control equipment. This is accomplished in a periodic inspection test, which involves tailpipe emissions measurements and a visual check for missing, broken, or tampered-with emissions control equipment. This dissertation has three related components with focus on vehicles emissions testing. The first of which, deals with estimated vehicles failure probabilities given vehicle characteristics, firm types, and firm's characteristics, using Fort Collins, Colorado, emissions inspection results in 2000 and 2002. I provide evidence of some discretion exercised among different firm types and firm organizational structure. The second part compares the effectiveness of emissions related repairs among competitive based emissions testing and command and control emissions testing facilities. Using emissions inspection test results for Fort Collins, Colorado, and Kenosha, Wisconsin, to represent the decentralized and centralized testing respectively, I show that emissions related repairs are more effective under centralized than decentralized configurations. This is attributed to the nature of both programs. The third component deals with an evaluation of inspection and maintenance programs in terms of efficiency and equity. I found that inspection and maintenance regulations have been successful in reducing emissions coming from newer vehicles but have been inefficient in terms of high administration costs and enticing motorist to repair and maintain their vehicles. I also found that the program place a particular burden on low income motorists. Also, I explored other proposals to correct for the deficiencies of inspection and maintenance programs, I found new vehicles sales tax and annual registration fee proposal is a suitable complementary tool to current program setting in order to lessen the problem of mobile emissions and achieve the goals of efficiency and equity.
Keywords: economics; automotive materials; environmental science